Testing and assessment of physical fitness of para athletes at Japan Institute of Sport Sciences - Hakamada, N.; Yanaka, T.; Yamamoto, M.; Shitara, K. (Journal of High Performance Sport, 2020)
The purpose of this article was to introduce fitness testing for Japanese para-athletes conducted at Japan Institute of Sports Sciences (JISS). Additionally, current challenges we face and our approaches for those challenges will be explained. Since 2015, fitness check-up for para-athletes have been carried out at JISS. The accumulated knowledge from scientific researches and know-how for supporting the Olympic sports for long time at JISS have been applied for Paralympic sports. Therefore, main fitness check-up services provided for the para-athletes have been similar to the Olympic athletes, which include body composition measurements, muscle strength tests, and aerobic and anaerobic capacity tests. However, the test protocols are modified and customized based on physical characteristics, or the types and degree of disabilities of each para-athlete. Their fitness levels and skills needed for their sports are assessed through tests that are specific to the sports. Our next challenges are to develop a testing method that can be customized for various types of disabilities for every sport and to establish fitness testing method with high accuracy for para-athletes.